PENGARUH PRODUCT ATTRIBUTE, REFERENCE GROUP, DAN BRAND TRUST TERHADAP BRAND LOYALTY PADA WARALABA DONAT DI JAKARTA BARAT - DEDY SUDARYONO; NUNO SUTRISNO (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to test and analyze empirically influence of Product Attribute, Reference Group, and Brand Trust to Brand Loyalty on donut franchise at West Jakarta. The object of this research is a donut franchise in West Jakarta. The purposive sampling technique is used in sample selection, where respondents who meet the criteria are analyzed using SPSS 20 program. The results showed that Reference Group and Brand Trust influenced Brand Loyalty, while Product Attribute had no effect on Brand Loyalty.